2012
DOI: 10.1371/journal.pone.0044686
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a High-Throughput Screen for Identifying Small Molecules to Activate the Keap1-Nrf2-ARE Pathway

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that induces a battery of cytoprotective genes involved in antioxidant defense through binding to Antioxidant Response Elements (ARE) located in the promoter regions of these genes. To identify Nrf2 activators for the treatment of oxidative/electrophilic stress-induced diseases, the present study developed a high-throughput assay to evaluate Nrf2 activation using AREc32 cells that contain a luciferase gene under the control of ARE pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…therapy. Indeed, several previous studies have described the exploration and identification of small molecules abrogating the pathway (36,37). However, it has also been shown that carcinogenesis, especially in the earliest stages, can be suppressed by the activation of NRF2, and many drugs enhance NRF2 activity (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…therapy. Indeed, several previous studies have described the exploration and identification of small molecules abrogating the pathway (36,37). However, it has also been shown that carcinogenesis, especially in the earliest stages, can be suppressed by the activation of NRF2, and many drugs enhance NRF2 activity (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cell‐based and in silico screens have identified Nrf2‐activating compounds (Schaap, Hancock, Wilderspin, & Wells, 2013; Wang et al, 2013; Williamson et al, 2012; Wu, McDonald, Liu, Chaguturu, & Klaassen, 2012), including triterpenoid 2‐cyano‐3,12‐dioxooleana‐1,9(11)‐dien‐28‐oate‐methylamide (CDDO‐MA), puerarin, sulforaphane, CDDO‐ethyl amide and others. Nrf2 activators demonstrated activity in in vitro and in vivo in different neurodegenerative mouse models, protecting neurons, decreasing the accumulation of aberrant proteins and increasing life span (Buendia et al, 2016; Joshi and Johnson 2012).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Under unstressed physiological conditions, Nrf2 is bound to the repressor Kelch-like ECH-associated protein 1 (Keap1) in the cytoplasm and easily degraded by ubiquitin-proteasome. 7 Upon activation, the Nrf2/Keap1 complex is dissociated, and Nrf2 is released from Keap1 and translocates into the nucleus, where it forms a heterodimer with its obligatory partner Maf and binds to the ARE sequence to activate transcription of a battery of antioxidant and cytoprotective genes, including heme oxygenase-1 (HO-1), NAD(P)H: quinine oxidoreductase 1 (NQO1), and γ-glutamate cysteine ligase. 8 Therefore, agents that modulate the Nrf2/ARE pathway would be expected to have beneficial effects in ameliorating oxidative stress-related diseases by upregulation of phase II antioxidant enzymes.…”
Section: Ye Et Almentioning
confidence: 99%
“…8 Therefore, agents that modulate the Nrf2/ARE pathway would be expected to have beneficial effects in ameliorating oxidative stress-related diseases by upregulation of phase II antioxidant enzymes. 7,8 The use of nanoparticles in biomedicine is currently an active area of research because nanoparticles hold great promise as novel and effective antioxidants for oxidative stress-related diseases. 9,10 The advantages of using nanoparticles as antioxidants over currently available antioxidants are due to the possibility that they have a versatile surface that can be decorated with active agents, 11 can penetrate the cell membrane, 12 can quench radicals without the need for assistance from other detoxifying molecules, 13 and possess higher physical stability in biological media, 14 thus extending their applications to the treatment of oxidative damage.…”
Section: Ye Et Almentioning
confidence: 99%